Religious Beliefs, Practices and Quality of Life among Cancer Survivors: A study on Cancer Survivor from Shaukat Khanam Cancer Hospital Lahore - Alvi, Aaqib Shahzad; Hussain, Intisar; Afzal, Afzaal; Rahman, Abdur (Pakistan Journal of Humanities and Social Sciences, 2023)
Religious belief and practices are meditative to assist people in confronting problems and an unrestrained prospect that absorbs connection to something greater, sacred, inspirational and intensively tied to a deep sense of entity. It is an integral dimension of an individual's life and recognized as a critical factor in their physical, psycho-social, cultural and health practices which deal with potentially life threatening and chronic diseases like cancer. Religious belief and practices have significant influences on the patient’s support system, emotional stability, enhance decision making, connectedness, acceptance, and even belief in survival among others. Religiosity among cancer patients/survivors manage life stressors and are linked to the notion of divinity; maintain relationship with God, reduction of negativity, improvement in health and quality of life. This empirical study was a cross-sectional research that carried out through the diagnostic survey methods and estimation. The primary data obtained from cancer survivors from Shaukat Khanam trust cancer hospital Lahore through Structured questionnaire along with DSES scale by Lynn G. Underwood (2006) and the scale of European organization for research and treatment of cancer (EORTC QLQ-C30). Findings of the study indicated that there is significant association between religious belief, practices and quality of life among cancer survivors.